2012
DOI: 10.1186/2046-1682-5-7
|View full text |Cite
|
Sign up to set email alerts
|

Arbitrary protein−protein docking targets biologically relevant interfaces

Abstract: BackgroundProtein-protein recognition is of fundamental importance in the vast majority of biological processes. However, it has already been demonstrated that it is very hard to distinguish true complexes from false complexes in so-called cross-docking experiments, where binary protein complexes are separated and the isolated proteins are all docked against each other and scored. Does this result, at least in part, reflect a physical reality? False complexes could reflect possible nonspecific or weak associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 59 publications
(74 reference statements)
2
58
0
Order By: Relevance
“…Out-of-frame sequences have similarly been used as a baseline to study the properties of BCR naive repertoires [16], or to estimate selective table 3.3 [29]). Residues that are exposed to solvent in protein-protein complexes (following definitions and data from [30]) are divided into three groups: surface (interface) residues that have unchanged accessibility area when the interaction partner is present (e), rim (interface) residues that have changed accessibility area, but no atoms with zero accessibility in the complex (f ) and core (interface) residues that have changed accessibility area and at least one atom with zero accessibility in the complex (g). Finally, we plot the basic biochemical amino acid properties (http://en.wikipedia.org/wiki/Amino_acid; http://en.wikipedia.org/wiki/Proteino genic_amino_acid): charge (h), pH (i), polarity ( j ), hydrophobicity (k) and volume (l ).…”
Section: Discussionmentioning
confidence: 99%
“…Out-of-frame sequences have similarly been used as a baseline to study the properties of BCR naive repertoires [16], or to estimate selective table 3.3 [29]). Residues that are exposed to solvent in protein-protein complexes (following definitions and data from [30]) are divided into three groups: surface (interface) residues that have unchanged accessibility area when the interaction partner is present (e), rim (interface) residues that have changed accessibility area, but no atoms with zero accessibility in the complex (f ) and core (interface) residues that have changed accessibility area and at least one atom with zero accessibility in the complex (g). Finally, we plot the basic biochemical amino acid properties (http://en.wikipedia.org/wiki/Amino_acid; http://en.wikipedia.org/wiki/Proteino genic_amino_acid): charge (h), pH (i), polarity ( j ), hydrophobicity (k) and volume (l ).…”
Section: Discussionmentioning
confidence: 99%
“…21, 2014; Fraction of positions Table 3.3 [17]). Residues that are exposed to solvent in protein-protein complexes (following definitions and data from [18]) are divided intothree groups: surface (interface) residues that have unchanged accessibility area when the interaction partner is present (D), rim (interface) residues that have changed accessibility area, but no atoms with zero accessibility in the complex (E) and core (interface) residues that have changed accessibility area and at least one atom with zero accessibility in the complex (F). Rim residues roughly correspond to the periphery of the interface region, and core residues correspond to the center.…”
Section: Appendix F: Shared Sequencesmentioning
confidence: 99%
“…Large‐scale modeling experiments dealing with hundreds of proteins can be computationally highly demanding and scaling up to thousands or tens of thousands of proteins asks for drastically reducing the computing time associated to molecular docking. In this respect, rigid‐body geometrical docking algorithms have been used to efficiently generate and rank candidate complex conformations . It has been suggested that docking scores based only on the geometric complementarity of the two molecular surfaces can be used to identify binding partners .…”
Section: Introductionmentioning
confidence: 99%
“…Some of these methods already provide very accurate predictions, without any knowledge of a protein's partner(s). Likewise, several docking studies showed that some regions at the surface of a protein are preferentially targeted by any protein (partner or not) . Nevertheless, a few recent works demonstrated that protein binding site predictions can be improved by including information about the native partner, provided that reliable structural data are available, and highlighted the specificity of interfaces involved in transient interactions .…”
Section: Introductionmentioning
confidence: 99%